Problematika Membaca Teks Arab Tanpa Harakat dan Solusinya untuk Meningkatkan Kemampuan Membaca Mahasiswa Pendidikan Bahasa Arab - Murzani Murzani; Salwa (Ameena Journal, 2026)
The ability to read unvowelized Arabic texts is one of the essential skills that must be mastered by students of Arabic Language Education in understanding various Arabic literature sources. However, in the learning process, many students still experience difficulties in reading Arabic texts without vowel marks accurately. These difficulties include low mastery of nahwu and sharaf, lack of reading practice, and low self-confidence when reading Arabic texts. Therefore, this study aims to analyze the problems faced by students in reading unvowelized Arabic texts and to examine solutions that can improve the reading ability of Arabic Language Education students. This study employed a library research method by collecting various data sources such as books, scientific journals, articles, and previous studies relevant to the research topic. The data were analyzed descriptively through the processes of collecting, understanding, classifying, and drawing conclusions based on the reviewed sources. The results of the study indicate that the problems in reading unvowelized Arabic texts are influenced by linguistic factors, lack of reading habits, and less optimal learning methods. In addition, the findings reveal that learning methods combining theoretical reinforcement with regular reading practice can help improve students’ reading abilities. Lecturer support, the use of appropriate teaching materials, and continuous reading habits are also important factors in enhancing students’ reading skills. This study contributes to the development of Arabic language learning, particularly in improving the ability to read unvowelized Arabic texts among Arabic Language Education students.